Adsorption Isotherms and Thermodynamics Studies for the Removal Methyl Orange from Wastewaters Using Multiwalled Carbon Nanotubes - Zhao, Donglin; Ding, Yi; Chen, Shaohua; Wang, Manli; Zhang, Xianglu (Asian Journal of Chemistry, 2014)
In this study, the adsorption of methyl orange on multiwalled carbon nanotubes from aqueous solutions was investigated in a batch stirred cell. The equilibrium adsorption data were analyzed using two common adsorption models: Langmuir and Freundlich. The results showed that Langmuir isotherm fit the experimental results well. Different thermodynamic parameters like enthalpy (DHº), Gibb’s free energy (DGº) and entropy (DSº) of the undergoing process were also evaluated through two adsorption models. The thermodynamic parameters (DHº, DSº and DGº) calculated from the temperature dependent adsorption isotherms indicated that the adsorption process of methyl orange on multiwalled carbon nanotubes was endothermic and spontaneous.